Nilai Skor CHA2DS2-VAS-HSF Sebagai Prediktor Kejadian Nefropati Yang Diinduksi Kontras Pada Pasien Sindroma Koroner Akut Yang Menjalani Prosedur Intervensi Koroner Perkutan - Herman William Parlindungan; Refli Hasan; Cut Aryla Andra; Nizam Zikri Akbar; Ali Nafiah Nasution; Harris Hasan; Zainal Safri; Anggia C Lubis; Bertha Gabriella Napitupulu (The Indonesian Heart Association, 2018)
Background: Contrast-Induced Nephropathy (CIN) is a serious problem that can be found in patients with acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI). The development of CIN in hospitalized patients even with coronary revascularization can immediately increase morbidity and mortality both during treatment and long-term outcomes. In a recent study, a CHA2DS2-VASC-HSF score was reported to predict coronary artery severity and major cardiovascular events (MACE) as well as CIN in AMI patients without atrial fibrillation. The purpose of this study was to investigate the CHA2DS2-VASC score as a predictor of CIN in AMI patients undergoing PCI procedures. Methods: This study was an ambispective cohort study of 53 AMI patients who were treated at cardiac care and underwent PCI procedures. The CHA2DS2-VASC-HSF score was calculated for each patient. From this study found 14 cases (26.4%) with a total CIN prevalence of 16.83%. CIN is defined as an increase in serum creatinine> 0.5 mg / dL or an increase in serum creatinine> 25% from baseline within 24 hours post PCI. Results: Through the analysis of the ROC curve, we established the CHA2DS2- VASC-HSF score cut point> 5 as a predictor of CIN with a sensitivity of 78.57% and specificity of 66.6 %% (AUC 0.818, 95%: CI 3.018-6.142, p <0.001). By getting the equation from the linear regression assessment we also found the probability of the occurrence of CIN in accordance with the CHA2DS2-VASC-HSF score. Conclusion: CHA2DS2-VASC score has a positive correlation with CIN. Therefore, this score can be used as a simple scoring system and can predict the incidence of CIN in AMI patients undergoing PCI procedures.